Kualitas Tidur dan Kestabilan Emosi dengan Hasil Prestasi Belajar pada Mahasiswa Fakultas Kedokteran - Candra Farid Rifai; Deviani Utami; Supriyati Supriyati; Achmad Farich (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Learning Achievement can be influenced by external and internal factors. The phenomenon of sleep deprivation and emotional stability fluctuations in medical students at Malahayati University has an impact on the quality of student lectures, so the Grade Point Average values cannot reach optimal values. So this is the concern of researchers to find out whether the relationship between these two factors affects the value of the student Grade. The research aims to determine the relationship between sleep quality and emotional stability with student achievement in the faculty of medicine Malahayati University Generation of 2018. The Respondents This research were students of the medical faculty of Malahayati University Generation 2018, a total of 168 students. The Sample is 118 students that use a purposive sampling technique. The questionnaire was used as a sleep quality questionnaire, emotional stability, and a second-semester transcript. Correlation test shows the relationship between sleep quality and learning achievement with P-Value 0,013 (<0,05) and emotional stability and learning achievement are 0,017 which means there is the relationship between sleep quality and emotional stability with achievement study.